Coefficient Convexity of Divisors of x^n-1 - Decker, Andreas; Moree, Pieter (Sarajevo Journal of Mathematics, 2024)
We say a polynomial fZ[x] is strongly coefficient convex if the set of coefficients of f consists of consecutive integers only. We establish various results suggesting that the divisors of x^n-1 that are in Z[x] have the tendency to be strongly coefficient convex and have small coefficients. The case where n=p^2q with p and q primes is studied in detail. 2010 Mathematics Subject Classification. 11B83, 11C08